Evolution or Revolution in EE/SE Research? A Collaborative Dialogue From First-Year PhD Students. (29th January 2016) - Beasy, Kim; Page, Leah; Emery, Sherridan; Ayre, Ian
Abstract: The AAEE 2014 research symposium in Hobart provided a privileged space for researchers and practitioners within environmental education and sustainability education (EE/SE) to come together and create dialogues about education for sustainability research. This essay is a critical reflection from postgraduate researchers about the symposium and the EE/SE research landscape more broadly. The authors interrogate contemporary research frameworks and practices, and deliberate on how current perceptions enable and inhibit performance within EE/SE research. The authors ask provocative questions and encourage readers to imagine for themselves what a new research landscape, freed of calcified frameworks and entrenched systems, might look like. The essay then draws on an ecological systems perspective as a means of reimagining EE/SE research within a more emergent landscape that values inclusivity, democracy, collaborative inquiry and curiosity.